2022
DOI: 10.3390/cancers14051329
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Three-Month Androgen Deprivation Therapy on [68Ga]Ga-PSMA-11 PET/CT Indices in Men with Advanced Prostate Cancer—Results from a Pilot Prospective Study

Abstract: Purpose: The purpose of this pilot prospective study is to examine the gallium-68-prostate-specific membrane antigen-11 ([68Ga]Ga-PSMA-11) positron emission tomography/computed tomography (PET/CT) imaging response in patients with advanced or metastatic hormone-naïve prostate cancer (PC) after 3 months of androgen deprivation therapy (ADT). Methods: We prospectively included men with untreated, clinical stage III or IV PC scheduled to receive ADT for at least 6 months. [68Ga]Ga-PSMA-11 PET/CT images were obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Shortterm ADT is known to increase PSMA expression in PCa cells, thereby increasing PSMA ligand uptake (36). In contrast, it has been reported that PSMA uptake decreases with long-term ADT, decreasing the sensitivity of PSMA PET for detecting PCa lesions (37,38). Furthermore, long-term ADT also reduces tumor cell numbers.…”
Section: Discussionmentioning
confidence: 97%
“…Shortterm ADT is known to increase PSMA expression in PCa cells, thereby increasing PSMA ligand uptake (36). In contrast, it has been reported that PSMA uptake decreases with long-term ADT, decreasing the sensitivity of PSMA PET for detecting PCa lesions (37,38). Furthermore, long-term ADT also reduces tumor cell numbers.…”
Section: Discussionmentioning
confidence: 97%
“…The acquisition protocol for 68 Ga-PSMA-11 PET/CT imaging has been previously described [9]. In brief, images were acquired on a GE Discovery MI PET/CT scanner (GE Healthcare, Milwaukee, WI, USA) 60 min after tracer injection (dose range: 103-182 MBq; median dose: 141 MBq).…”
Section: Pet/ct Imagingmentioning
confidence: 99%
“…A Bayesian penalized likelihood algorithm (Q.Clear) was used for image reconstruction. Methods for image calibration included attenuation correction, the point spread function, and the QCHD-S technique [9].…”
Section: Pet/ct Imagingmentioning
confidence: 99%
See 2 more Smart Citations